Gender, agriculture, and assets project (GAAP) - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
GAAP’s objective is to better understand gender and asset dynamics in agricultural development programs. GAAP core team members works with agricultural development projects in South Asia and Sub Saharan Africa to: identify how development projects impact men’s and women’s assets; clarify which strategies have been successful in reducing gender gaps in asset access, control and ownership; and improve partner organization’s abilities to measure and analyze qualitative and quantitative gender and assets data in their monitoring and evaluation (M&E) plans for current and future projects.